VD_FINDINFO HC / 2010 / 718 vom 22. November 2010 - VD Tribunal cantonal (2010)
CONTRAT DE TRAVAIL, RÉSILIATION | 336 al. 1 let. a CO, 336 al. 1 let. d CO, 452 al. 1ter CPC, 452 al. 2 CPC, 452 CPC, 46 al. 1 LJT, 46 al. 2 LJT, 46 LJT